2016
DOI: 10.1097/olq.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Extragenital Chlamydia and Gonorrhea in Women and Men Who Have Sex With Men Reporting a History of Receptive Anal Intercourse

Abstract: Background Screening for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (GC) in men who have sex with men (MSM) is risk-based. Despite high frequencies of oral and receptive anal intercourse (RAI) among women, extragenital screening is not recommended. Methods Women (n=175) and MSM (n=224) primarily recruited from a sexually transmitted infections clinic reporting a lifetime history of RAI completed a structured questionnaire and clinician collected swab samples from the rectum, pharynx, vagina (women)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 27 publications
2
65
1
Order By: Relevance
“…Horizontal transfer between hosts, via the oral-fecal route has been recorded as well, while shedding infectious chlamydial particles through feces is highly prevalent in livestock and other animal models. Whereas most data in regards to rectal C. trachomatis infections was reported in high risk patients such as men who have sex with men, recent studies report a high prevalence in women as well [135,136]. A study in two Canadian sexual health clinics found that 82.4% (n= 433) of the C. trachomatis positive patients were rectal positive, while 30% of Chlamydia cases were positive solely at the rectal site [136].…”
Section: How Chlamydia Can Utilize the Microbiome To Overcome Host Immentioning
confidence: 93%
“…Horizontal transfer between hosts, via the oral-fecal route has been recorded as well, while shedding infectious chlamydial particles through feces is highly prevalent in livestock and other animal models. Whereas most data in regards to rectal C. trachomatis infections was reported in high risk patients such as men who have sex with men, recent studies report a high prevalence in women as well [135,136]. A study in two Canadian sexual health clinics found that 82.4% (n= 433) of the C. trachomatis positive patients were rectal positive, while 30% of Chlamydia cases were positive solely at the rectal site [136].…”
Section: How Chlamydia Can Utilize the Microbiome To Overcome Host Immentioning
confidence: 93%
“…As previously reported from this study population, nearly 80% of chlamydial and gonococcal infections in men and 16 to 18% of these infections in women were detected only in the pharynx or rectum (14). Extragenital testing for STIs should be considered, especially for men who have sex with men, in whom most infections occur at extragenital sites.…”
Section: Discussionmentioning
confidence: 68%
“…Urogenital-only testing would have missed 80% of the C. trachomatis-positive and 77% of the N. gonorrhoeae-positive samples in males. In contrast, 82% of the total chlamydial infections and 83% of the total gonococcal infections in women were detected using the vaginal sample alone (14). …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations